2020
DOI: 10.1155/2020/4326840
|View full text |Cite
|
Sign up to set email alerts
|

Edible Coating Based on Roselle (Hibiscus sabdariffaL.) Mucilage Applied to Soursop Fruits in Postharvest Storage

Abstract: The soursop fruit (Annona muricata L.) is a crop of significant economic value for Nayarit, which is characterized by having a bittersweet taste, making it attractive to the consumer. However, the soursop has rapid maturation which causes a short shelf life. Several postharvest management techniques have been applied to reduce its metabolic processes, such as refrigeration, use of 1-methylcyclopropene (1-MCP), and controlled and modified atmospheres. In recent years, polysaccharide-based coatings have been app… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 61 publications
0
4
0
Order By: Relevance
“…The literature reported that the application of edible coatings mucilage enhanced the quality parameters and elongated the shelf life [13] of okra mucilage [14,15]. *Corresponding author e-mail: ahmed.abdallah@agr.cu.edu.eg .…”
Section: Introductionmentioning
confidence: 99%
“…The literature reported that the application of edible coatings mucilage enhanced the quality parameters and elongated the shelf life [13] of okra mucilage [14,15]. *Corresponding author e-mail: ahmed.abdallah@agr.cu.edu.eg .…”
Section: Introductionmentioning
confidence: 99%
“…The levels of SS in the coated mango decreased because the coatings decreased the rate of respiration, leading to the slow ripening of the fruit (Wei;Mei;Xie, 2021). The levels of SS increased, despite the action of the coatings, because temperature favored the enzymatic reactions, inducing the hydrolysis of starch to sugars (De los Santos-Santos et al, 2020).…”
Section: Physicochemical Attributesmentioning
confidence: 99%
“…This was probably due to delayed synthesis and accumulation of β-carotene because of lowering O 2 and increasing CO 2 concentrations. On the other hand, the total phenolics and vitamin C contents were increased in soursop fruits coated with roselle mucilage (2%) and stored at 15°C for eight days (De los Santos-Santos et al, 2020). The role of different coatings on antioxidant capacity is related to their effect on delaying fruit ripening and extending their shelf life.…”
Section: Coatingsmentioning
confidence: 99%